Fallen women [large type] - Dallas, Sandra (Center Point Large Print, 2013)
It is the spring of 1885 and wealthy New York socialite Beret Osmundsen has been estranged from her younger sister, Lillie, for a year when she gets word from her aunt and uncle that Lillie has died suddenly in Denver. What they do not tell her is that Lillie had become a prostitute and was brutally murdered in the brothel where she had been living. When Beret discovers the sordid truth of Lillie's death, she makes her way to Denver, determined to find her sister's murderer. Detective Mick McCauley may not want her involved in the case, but Beret is determined, and the investigation soon takes her from the dangerous, seedy underworld of Denver's tenderloin district to the highest levels of Denver society. Along the way, Beret will not only learn the depths of Lillie's depravity, but will also expose the darkest side of Gilded Age ambition in the process.